2016
DOI: 10.1097/fbp.0000000000000258
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin for the treatment of drug and alcohol use disorders

Abstract: There is growing interest in the use of oxytocin (OT) as a potential treatment for alcohol and other substance use disorders. OT is a neuropeptide that modulates adaptive processes associated with addiction including reward, tolerance, associative learning, memory, and stress responses. OT exerts its effects via interactions with the hypothalamic–pituitary–adrenal (HPA) axis, and multiple neurotransmitter systems including the dopamine mesolimbic reward and corticotrophin-releasing factor stress systems. Oxyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 126 publications
0
70
0
2
Order By: Relevance
“…Oxytocin may play a role in the pathophysiology of alcohol use disorders [16, 17], and may block the effects of methamphetamine and cocaine [55]. A similar effect has also been found in opioid addiction [4, 5].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Oxytocin may play a role in the pathophysiology of alcohol use disorders [16, 17], and may block the effects of methamphetamine and cocaine [55]. A similar effect has also been found in opioid addiction [4, 5].…”
Section: Discussionmentioning
confidence: 91%
“…The effect of oxytocin on the dopaminergic system may also facilitate social interaction, which exerts a protective effect against addiction [6, 15]. Although it is as yet unclear whether oxytocin and dopamine have a direct association, accumulating evidence has suggested that oxytocin may have a positive effect on treatment for alcohol use disorders and other problematic substance abuse [16, 17]. In addition, there could exist an association between dopamine and novelty-seeking tendency [18], which could be an important issue related to addiction and oxytocin [19-21].…”
Section: Introductionmentioning
confidence: 99%
“…Da Oxytocin als sicher einsetzbares Medikament gilt, werden derzeit dessen Effekte bei verschiedenen Suchterkrankungen intensiv untersucht [59]. Dabei sollten die Beeinflussung der CRF-Systeme durch Oxytocin und dessen Effekte auf angst-und stressassoziierte Suchtmechanismen beleuchtet werden.…”
Section: Schlussfolgerungen Und Perspektivenunclassified
“…The increasing body of evidence shows that stress exposure is an important contributing factor to drug dependence and suggests that cortisol release induced by stress of withdrawal, increases drug reinforcement. Our clinical data suggest that the OT may be useful to reduce craving and withdrawal symptoms through its effects on the HPA axis and attenuating stress-related physiological and subjective response [16]. Our results indicate that OT does not affect subjective self-reporting of anxiety.…”
Section: Discussionmentioning
confidence: 46%
“…Cortisol and DHEAS and especially cortisol/DHEAS ratio are assaying as neuroadaptive stress hormones to predict health outcome [14,15]. Given the established strong link between stress, drug use and relapse as along with the known dysregulation of hypothalamic pituitary adrenal (HPA) axis activity associated with substance-use disorders [16], the effects of OT on the stress system have received a lot of attention. Therefore, the current study was designed to evaluate the acute effect of OT administration on withdrawal, craving, anxiety scores, and neuroadaptive stress hormones levels in the male heroin-dependent individuals.…”
Section: Introductionmentioning
confidence: 99%